PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP RISIKO KREDIT PERUSAHAAN NON KEUANGAN - Cendikia Paranandhi; Haryanto Haryanto (Diponegoro Journal of Accounting, 2013)
This study aims to examine how the effect of implementation of good corporate governance of the credit risk of non-financial firms. Specifically, this study analyzed the effect of GCG proxied by corporate governance perception index (CGPI) to the credit risk, which is proxied by credit rating and DER. The population of this research are consists of companies listed on Indonesia Stock Exchange in the year 2006-2011. The samples in this study were selected using purposive sampling, consisting of non-financial firms that following assessment scores CGPI by IICG through SWA magazine and has issued bonds in 2006-2011. This study used ordinal logistic regression analysis model to examine the effect of the implementation of good corporate governance on bond ratings and simple linear regression to examine the effect of the implementation of good corporate governance to the DER.The results of this study indicate that scores CGPI has significantly positive impact on bond rating. This study also indicate that scores CGPI has significantly negative impact on DER.